Ethereum cookbook : over 100 recipes covering Ethereum-based tokens, games, wallets, smart contracts, protocols, and Dapps - Mukhopadhyay, Mayukh (Packt Publishing, 2018)
Mine Ether, deploy smart contracts, tokens, and ICOs, and manage security vulnerabilities of Ethereum Key Features Build end-to-end decentralized Ethereum apps using Truffle, Web3, and Solidity Explore various solution-based recipes to build smart contracts and foolproof decentralized applications Develop decentralized marketplaces from scratch, build wallets, and manage transactions Book Description Ethereum and Blockchain will change the way software is built for business transactions. Most industries have been looking to leverage these new technologies to gain efficiencies and create new business models and opportunities. The Ethereum Cookbook covers various solutions such as setting up Ethereum, writing smart contracts, and creating tokens, among others. You'll learn about the security vulnerabilities, along with other protocols of Ethereum. Once you have understood the basics, you'll move on to exploring various design decisions and tips to make your application scalable and secure. In addition to this, you'll work with various Ethereum packages such as Truffle, Web3, and Ganache. By the end of this book, you'll have comprehensively grasped the Ethereum principles and ecosystem. What you will learn Efficiently write smart contracts in Ethereum Build scalable distributed applications and deploy them Use tools and frameworks to develop, deploy, and test your application Use block explorers such as Etherscan to find a specific transaction Create your own tokens, initial coin offerings (ICOs), and games Understand various security flaws in smart contracts in order to avoid them Who this book is for The Ethereum Cookbook is for you if you are a software engineer, Blockchain developer, or research scientist who wants to build smart contracts, develop decentralized applications, and facilitate peer-to-peer transaction. It is assumed that you are familiar with Blockchain concepts and have sound knowledge of JavaScript.